2020
DOI: 10.5267/j.msl.2019.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting domestic credit growth based on ARIMA model: Evidence from Vietnam and China

Abstract: Credit is an economic category and is also a product of the commodity economy, which exists through many socioeconomic forms to promote economic growth. Therefore, the objective of this paper is to analyst, compare and forecast domestic credit growth in Vietnam's and China's economy. Thus, the paper is applied by a method of an autoregressive integrated moving average (ARIMA) model. This model is fitted to time series data both to better understand the data and to forecast future points in the series. Hereby, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Endogenous variable impact analysis is to assess the volatility of oil prices itself and economic growth, the events of 2008 showed that the volatility of oil prices is a source of exogenous volatility, but influences Financial benefit is an endogenous variable. Besides, the oil-rich countries have the impact of their financial crisis when their economic growth has depended on continuously falling oil prices (Uchechukwu et al, 2019;Dinh, 2020c).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Endogenous variable impact analysis is to assess the volatility of oil prices itself and economic growth, the events of 2008 showed that the volatility of oil prices is a source of exogenous volatility, but influences Financial benefit is an endogenous variable. Besides, the oil-rich countries have the impact of their financial crisis when their economic growth has depended on continuously falling oil prices (Uchechukwu et al, 2019;Dinh, 2020c).…”
Section: Literature Reviewmentioning
confidence: 99%
“…ℎ = 2,3, … , 𝑛𝑛, where h and n are the forecasting horizon and the number of out-of-sample time series data. Therefore, the forecasting horizons that have been applied in the study are 2, 3, 4, 5, 7, 10, 15, 20, 25, 30 and 45-days ahead of the overnight IIR [6][7] and [16][17][18][19]. Consequently, a (1 − 𝛼𝛼)100% PIs for h-step ahead forecasting and 𝑎𝑎 𝑡𝑡 follows normal distribution is given by Equation 11.…”
Section: Stage Iv: Forecastingmentioning
confidence: 99%
“…Regression analysis is like other deductive methods. The objective of the paper is to collect a random sample from the GDP growth and inflation rate and use it to estimate their characteristic (Dinh, 2020a).…”
Section: Literature Reviewmentioning
confidence: 99%